Investigation on the Effects of Glycerol and Clay Contents on the Structure and Mechanical Properties of Maize Starch Nanocomposite Films. (14th January 2020) - Mansour, Gabriel; Zoumaki, Maria; Marinopoulou, Anna; Raphaelides, Stylianos N.; Tzetzis, Dimitris; Zoumakis, Nikolaos
Abstract: Nanocomposite films are prepared using normal maize starch, plasticized with glycerol and water and three different types of montmorillonite clay employing the solution method. A series of samples with different compositions is prepared by varying the concentrations of glycerol and nanoclay. The tensile properties of films are investigated as a function of clay and plasticizer contents. The experimental results indicate a significant improvement in the mechanical properties of nanocomposite films prepared with sodium montmorillonite clay as compared to commercial organoclay and Kimolian montmorillonite clay. ANOVA tests and regression models indicate that both glycerol and clay contents influence significantly the mechanical properties of films, and the tensile properties of nanocomposite films are enhanced even at lower clay content. The best results are obtained with nanocomposites at glycerol concentration of about 20 wt% and clay content of about 10 wt%. The intercalated nanocomposite structure of the films is ascertained by wide angle XRD analysis whereas the morphology of samples is examined by scanning electron microscopy, optical microscopy, and confocal laser scanning microscopy. Abstract : The effects of glycerol and nanoclay contents on the mechanical properties of native normal maize starch biocomposites are investigated. Nanocomposite films are prepared using maize starch, plasticized with glycerol and water and three different types of montmorillonite clay. The best results are obtained with sodium montmorillonite nanocomposites at glycerol concentration of about 20 wt% and clay content of 10 wt%.